2008
DOI: 10.1111/j.1473-6861.2008.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of health sciences students towards interprofessional teamwork and education

Abstract: Relatively little is known about the specific attributes of health professional students which may influence their attitudes towards both interprofessional teamwork and interprofessional education. A survey was distributed to all pre‐licensure health professional students from medicine, nursing, pharmacy and social work programmes at our institution. Respondents were asked to rate their attitudes towards interprofessional healthcare teams and interprofessional education using validated and reliable scales repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 21 publications
10
134
3
2
Order By: Relevance
“…28 Our finding that medical students scored lower on their attitudes toward collaborative relationship than pharmacy students has implications for interdisciplinary education and interprofessional collaboration. More research is needed to confirm our results in students and practitioners at multiple institutions.…”
Section: Discussionmentioning
confidence: 79%
“…28 Our finding that medical students scored lower on their attitudes toward collaborative relationship than pharmacy students has implications for interdisciplinary education and interprofessional collaboration. More research is needed to confirm our results in students and practitioners at multiple institutions.…”
Section: Discussionmentioning
confidence: 79%
“…[28][29][30][31][32][33] In the case of students, pharmacy and social work students expressed more positive attitudes toward interprofessional collaboration than did medical students. 34 In one study, however, Turkish medical students demonstrated a more positive attitude toward collaboration than did nursing students. 35 Despite the possible force of the principle of least interest, we show that prospective health professions students, the vast majority of whom aspire to become medical or dental physicians, could be influenced to become significantly more eager to collaborate with pharmacists simply through working regularly with pharmacy students to perform critical-thinking and reflection exercises in biochemistry learning teams.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores represent more positive attitudes toward interprofessional learning. The modified RIPLS has been found to have very good internal consistency when completed by health professional students [28,29]. Two underlying constructs have been identified: 'expertise'; and 'competency' [28].…”
Section: Attitudes Toward Interprofessional Learningmentioning
confidence: 99%